2014
DOI: 10.5937/ekopolj1403603p
|View full text |Cite
|
Sign up to set email alerts
|

Competitiveness of destinations within the rural tourism cluster: Zlatar, Zlatibor

Abstract: Summary Cluster analysis is gaining increasing importance in the contemporary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…On the other hand, the results of this analysis are congruent with past studies where accommodation quality is found positively related to rural tourism destination competitiveness (Dębski and Niemczak, 2016; Pavlovic and Cavlin, 2014; Ritchie and Crouch, 2010), and thus H2 is supported undeniably. One plausible reason is that tourists who visited the rural tourism destination would like to spend their time for at least an overnight stay in rural destination in order for them to have the real feeling of staying at a homestay.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…On the other hand, the results of this analysis are congruent with past studies where accommodation quality is found positively related to rural tourism destination competitiveness (Dębski and Niemczak, 2016; Pavlovic and Cavlin, 2014; Ritchie and Crouch, 2010), and thus H2 is supported undeniably. One plausible reason is that tourists who visited the rural tourism destination would like to spend their time for at least an overnight stay in rural destination in order for them to have the real feeling of staying at a homestay.…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, accommodation quality is also found to be the significant component on tourism destination competitiveness, which is other than tourism infrastructure (Pavlovic and Cavlin, 2014; Ritchie and Crouch, 2010). As per documented by past studies, both accommodation facilities and accessibility quality of a tourism destination are the prior determinants of tourists’ intention in a way to visit tourism destination (Dębski and Niemczak, 2016; Dwyer and Kim, 2003).…”
Section: Literature Review and Theoretical Foundationmentioning
confidence: 99%
“…So far, research about rural tourism development in Serbia was taken from the side perspective, dealing with different subjects: competitiveness (Demirović, Košić, Surd, Žunić, & Syromiatnikova, 2017;Pavlović & Čavlin, 2014;Petrović et al, 2018;Vujko, Petrović, Dragosavac, & Gajić, 2016), possible development potentials (Djenadić, Muhi, & Jovanović, 2016;Todorović & Bjeljac, 2009), possible financial sources for development (Radović, 2016), the role of the local population (Košić, Demirović & Dragin, 2017;Vuković, Subić, & Cvijanović, 2014), etc. Little is known about who visits rural areas and what attracts them.…”
Section: Introductionmentioning
confidence: 99%
“…Attractions and activities that are considered as the basis of tourism clusters have a positive foothold, based on the experience from all over the world through theme paths, routes, or simply branding of an entire geographic region, such as Tuscany in Italy, Silicon Valley in the US or Provence in France. There is extensive literature on the thematic trails of countries in Europe that have been used to develop rural tourism, whether in Montenegro , Macedonia (Petrevska et al, 2013), Serbia (Pavlović & Čavlin, 2014), Sweden (Nordin, 2003), or Italy (Babalola et al, 2011).…”
Section: Selective Forms Of Tourismmentioning
confidence: 99%
“…Many authors give recommendations for tourism cluster models that are specific to their countries and regions. In Serbia, for example, tourism clusters include sub-areas or micro-destinations within a region that have similar tourist value (Pavlović & Čavlin, 2014). Their Master Plan for the Sustainable Development of Rural Tourism was adopted in 2011 and covered the development of 12 rural tourism clusters, grouped into four rural tourism groups that are divided by regions in Serbia.…”
Section: Tourism Clustersmentioning
confidence: 99%